100 Jahre Einkristallzucht aus der Schmelze: Vom Spreeknie ins Silicon Valley - Evers, Jürgen; Herzog, Christiane; Möckl, Leonhard; von Plotho, Christoph; Stallhofer, Peter; Staudigl, Rudolf (Chemie in Unserer Zeit, 2016)
Cars, television, mobile phones, digital cameras, cash machines: Daily life is strongly affected by microchips produced from high purity silicon single crystals via thin wafers. Most of these single crystals are prepared by a process invented by the German-Polish scientist Jan Czochralski in 1916 in the “Kabelwerk Oberspree (KWO)” of the “Allgemeine Elektricitätsgesellschaft (AEG)” in Berlin-Oberschöneweide. Czochralski discovered the famous method to pull single crystals by accident: Deep in thought, he dipped his pen not into an ink pot but into a crucible with liquid tin, both standing next to one another on his desk. Quickly he pulled his pen out and observed a thin thread of tin emerging from the tip. After etching, the thread was identified as a single crystal of tin. This observation is probably one of the most important technical inventions of the first half of the 20thcentury. In 1917, he left the AEG in Berlin and worked in the metal research laboratory, later belonging to the “Metallgesellschaft”, in Frankfurt/Main. Until today, wafers of high-purity silicon are prepared by the Czochralski method. Silicon wafers with 200 mm diameter were produced in 1990, 300 mm wafers in 2001. The production of wafers with 450 mm diameter was expected for 2016. Siltronic produced in 2009 the first dislocation-free silicon single crystal with 450 mm diameter, and other companies followed. However, until now, the 450 mm technology is not standard. This is due to a combination of very high investment costs needed to establish the 450 mm technology and very low prices of microchips.
CRIS-Team Scopus Importer:2024-09-09